1998
DOI: 10.1021/bi973121t
|View full text |Cite
|
Sign up to set email alerts
|

Menaquinone-7 in the Reaction Center Complex of the Green Sulfur BacteriumChlorobium vibrioformeFunctions as the Electron Acceptor A1

Abstract: Photosynthetically active reaction center complexes were prepared from the green sulfur bacterium Chlorobium vibrioforme NCIMB 8327, and the content of quinones was determined by extraction and high-performance liquid chromatography. The analysis showed a stoichiometry of 1.7 molecules of menaquinone-7/reaction center. No other quinones were detected in the isolated reaction centers, whereas membrane preparations also contained chlorobiumquinone. The possible involvement of quinones in electron transport was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The loss of PsaB-Trp673 implies that GsbRC lost the asymmetry in the energetics of the electron transfer pathways via quinone at the A 1 site. Frigaard et al and Takaichi and Oh-oka reported that one or two quinones might bind to GsbRC and serve as A 1 . In contrast, no quinone was detected in analysis using high-performance liquid chromatography and ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry, according to Chen et al From the fact that phylloquinone is always unambiguously modeled in the reported PSI crystal structures (e.g., refs , ), it seems plausible that the quinone binding is less pronounced in GsbRC than PSI.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of PsaB-Trp673 implies that GsbRC lost the asymmetry in the energetics of the electron transfer pathways via quinone at the A 1 site. Frigaard et al and Takaichi and Oh-oka reported that one or two quinones might bind to GsbRC and serve as A 1 . In contrast, no quinone was detected in analysis using high-performance liquid chromatography and ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry, according to Chen et al From the fact that phylloquinone is always unambiguously modeled in the reported PSI crystal structures (e.g., refs , ), it seems plausible that the quinone binding is less pronounced in GsbRC than PSI.…”
Section: Resultsmentioning
confidence: 99%
“… 5 The PscA protein carries the primary donor P840 (a special pair of BChl a molecules), the primary electron acceptor A 0 (Chl a 670), a possible secondary electron acceptor A 1 (menaquinone), and Fe–S center X (F X ). 1 , 5 , 7 , 8 The PscB protein binds two 4Fe–4S centers called F A and F B as the terminal electron acceptors. The PscC protein, which mediates the transfer of an electron from the menaquinol/cytochrome c oxidoreductase to P840, has three membrane-spanning regions at the N-terminal end and a soluble domain that binds a single heme group at the C-terminal end on the periplasmic side of the membrane.…”
mentioning
confidence: 99%